Molecular classification and phylogenetic relationships of selected edible Basidiomycetes species - Avin, F.A.; Bhassu, S.; Shin, T.Y.; Sabaratnam, V. (2012)
Morphological identification of edible mushrooms can sometimes prove troublesome, because phenotypic variation in fungi can be affected by substrate and environmental factors. One of the most important problems for mushroom breeders is the lack of a systematic consensus tool to distinguish different species, which are sometimes morphologically identical. Basidiomycetes as one of the largest groups of edible mushrooms have become more important in recent times for their medicinal and nutritional properties. Partial rDNA sequences, including the Internal Transcribed Spacer I-5.8SrDNA-Internal Transcribed Spacer II, were used in this study for molecular identification and assessment of phylogenetic relationships between selected edible species of the Basidiomycetes. Phylogenetic trees showed five distinct clades; each clade belonging to a separate family group. The first clade included all the species belonging to the Pleurotaceae (Pleurotus spp.) family; similarly, the second, third, fourth, and fifth clades consist of species from the Agaricaceae (Agaricus sp.), Lyophllaceae (Hypsigygus sp.), Marasmiaceae (Lentinula edodes sp.) and Physalacriaceae (Flammulina velutipes sp.) families, respectively. Moreover, different species of each family were clearly placed in a distinct sub-cluster and a total of 13 species were taken for analysis. Species differentiation was re-confirmed by AMOVA analysis (among the populations: 99.67%; within: 0.33%), nucleotide divergence, haplotyping and P value. Polymorphism occurred throughout the ITS regions due to insertion-deletion and point mutations, and can be clearly differentiated within the families as well as genera. Moreover, this study proves that the sequence of the ITS region is a superior molecular DNA barcode for taxonomic identification of Basidiomycetes.